INFLUENCE OF FOREST RENEWAL FELLINGS ON THE PROCESSES OF THE NATURAL PINE FOREST REPRODUCTION IN THE NORTHERN STEPPE - Tkach, V. P.; Tarnopilska, O. M.; Manoilo, V. O. (Forestry and Forest Melioration, 2018)
The paper gives the results of studies concerning forest renewal fellings in the pine forest stands excluded from the main use in the Northern Steppe of Ukraine. It is established that for preservation of biological diversity and genetic potential of the forests, and also for their natural reproduction it is expedient to implement close to nature forestry actions. It is especially actual for the natural pine forests of Izyumsky near-Steppe pine forest which carry out unique ecological functions. For the purpose of reproduction of these forests the forest renewal fellings by a group-gradual method are expedient. In conjunction with the measures for assistance to natural renewal and its preservation these fellings create favorable conditions for the reproduction of valuable pine forests.